On Taleb on Ricardo: A clarification - Futerman, Alan; Block, Walter (REVISTA PROCESOS DE MERCADO, 2019)
In the present work, Ricardo’s Law of Comparative Advantage (also known as “Law of Association”) is analyzed in order to critically respond to the analysis offered by Taleb (2012). The latter points to the invalidity of the model, since it does not assume price variability, thus exposing it to grave sys- temic consequences due to abrupt changes in relative prices. Our critique is based on the approach taken by Ludwig Von Mises (1949) on the same sub- ject. The Ricardian model is viewed from a praxeological perspective. We maintain that Taleb’s critique, although correct in invalidating Ricardo’s anal- ysis, not only does not harm but even reaffirms Ricardo’s original conclusion pointing to the advantages of cooperation in general, and international free trade in particular. Keywords: Taleb, Mises, International Trade, Comparative Advantage, Ricardo. JEL classification: F19. Resumen: En este trabajo, la ley de Ricardo sobre ventaja comparativa (también conocida como ley de asociación), es analizada para responder de forma crítica al análsis ofrecido por Taleb (2012). Éste último, apunta a la invalidez del modelo, ya que no asume la variablidad de precios, exponiéndolo así a graves conse- cuencias sistématicas debido a los cambios abruptos en los precios relativos. Nuestra crítica se basa en el enfoque de Ludwig Von Mises (1949) sobre este tema. El modelo ricardiano se observa desde una perspectiva praxeológica. Sostenemos que la crítica de Taleb, aunque correcta para invalidar el análisis de Ricardo, no sólo no perjudica sino que incluso reafirma la conclusión original de Ricardo que señala las ventajas de la cooperación en general, y el libre comercio internacional en particular. Palabras clave: Taleb, Mises, Comercio internacional, Ventaja comparativa, Ricardo. Clasificación JEL: F19.